A retrospective analysis of the increase in syphilis incidence in the Russian Federation in 2009–2023 and trends in dynamic development of epidemiological processes - Margarita R. Rakhmatulina; Lidia Е. Melekhina; Elena Yu. Novoselova (Vestnik Dermatologii i Venerologii)
The problem of syphilis incidence has been relevant throughout all times and remains so to this day. The level of incidence is a key indicator of the epidemiological situation regarding the spread of syphilis among the population. Over the past five years, the Russian Federation has experienced variability in syphilis incidence rates after a prolonged decline from 2009 to 2020. The assessment of the epidemiological situation regarding syphilis allows us to state that, overall, there is a stabilization of the epidemiological process in the country, characterized by a regression in incidence rates and a restoration of the trend towards further reduction. It is also evident that the observed increase in syphilis incidence in the Russian Federation was associated with a rise in the number of foreign nationals, including migrants, infected with syphilis, against the backdrop of a decrease in syphilis incidence among Russian citizens.